(untitled) (Communications in Computational Physics, 2011)
The low temperature properties of double exchange model in triangular lattice are investigated via truncated polynomial expansion method (TPEM), which reduces the computational complexity and enables parallel computation. We found that for the half-filling case a stable 120◦spin configuration phase occurs owing to the frustration of triangular lattice and is further stabilized by antiferromagnetic (AF) superexchange interaction, while a transition between a stable ferromagnetic (FM) phase and a unique flux phase with small finite-size effect is induced by AF superexchange interaction for the quarter-filling case.